2021
DOI: 10.1158/1078-0432.ccr-20-4135
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Ligands, the Forgotten Triggers of Nuclear Receptor Action; Implications for Acquired Resistance to Endocrine Therapy

Abstract: Purpose: There is strong epidemiologic evidence indicating that estrogens may not be the sole steroid drivers of breast cancer. We hypothesize that abundant adrenal androgenic steroid precursors, acting via the androgen receptor (AR), promote an endocrineresistant breast cancer phenotype.Experimental Design: AR was evaluated in a primary breast cancer tissue microarray (n ¼ 844). Androstenedione (4AD) levels were evaluated in serum samples (n ¼ 42) from hormone receptor-positive, postmenopausal breast cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The expression of prostate-specific antigen, a representative androgen-induced gene, is increased in recurrent tissues. In addition, a recent transcriptional analysis revealed an increased ratio of AR:ERα signaling pathway activities in patients failing AI therapy ( Bleach et al 2021 ). These findings suggest that increased androgen action is closely linked to AI resistance.…”
Section: Androgens and Therapeutic Resistance In Breast Cancermentioning
confidence: 99%
“…The expression of prostate-specific antigen, a representative androgen-induced gene, is increased in recurrent tissues. In addition, a recent transcriptional analysis revealed an increased ratio of AR:ERα signaling pathway activities in patients failing AI therapy ( Bleach et al 2021 ). These findings suggest that increased androgen action is closely linked to AI resistance.…”
Section: Androgens and Therapeutic Resistance In Breast Cancermentioning
confidence: 99%
“…A recent trial NCT02007512 using the AI exemestane, with or without enzalutamide, in patients with ER+ advanced/metastatic disease found that high levels of AR and low levels of ESR1 were associated with the significantly greater benefit of enzalutamide 20 . These complexities emphasize the importance of clinical context and hormonal milieu when considering AR action in BC 21 . Clearly, AR does influence BC biology, and high AR relative to ER levels can serve as an independent predictor of response to anti-estrogen therapies, perhaps by identifying tumors poised to escape ER-directed therapies and switch to survival dependent on androgens and AR.…”
Section: Introductionmentioning
confidence: 99%